Economic limit calculate method of blocked layer released by water flood wells - Fulin Wang (PLoS ONE, 2025)
Daqing Oilfield is in the forefront, because of polymer flooding well pattern was used to next production layer, so, first development layer was sealed after polymer well was used to next layer, and whose storage reserves is very huge. To 2021, OOIP of the first set of reserves of type II reservoirs has been sealed up to 9603 × 104 t. In order to release the reserves and reduce the influence on oil yield, water drive well pattern was used to product the sealed reserves through additional perforating, but the economic boundary standard to release the sealed layer using water drive well pattern is not determined, so, based on the principle of break-even and the seepage flow theory, this paper establishes the formula for calculating the economic limits of the various unsealing indexes by water flood well, which can effectively solve the problem of communicating and understanding the economic and engineering parameters of the released well, quantificational the limit of layer selection standard of well for releasing. The result showed the cumulative and daily oil production limit is gradually decreases with oil prices increasing, and vertically, the limit is increases with the input-output ratio (ROI) increases. FWHP of oil well b1-40-527 is 0.4 Mpa, well spacing is 300 m, oil well radius is 0.1 m, viscosity is 8.8 mPa. s, production time of 300 d, density of 0.86 g/cm3, when ROI is 1:2, the lower limit of the cumulative oil raised production is 206.9 t and daily increasing oil floor is 0.69 t/d, the minimum released effective thickness is 8.4 m as oil price is 60 $/BBL, meanwhile, the lower limit of the cumulative oil raised production is 421.4 t and daily increasing oil floor is 1.4 t/d when oil price is 40 $/BBL. After increasing the thickness of released layer according the limit, it is verified by actual data, that the increasing oil production of daily and accumulated reached to the calculation minimum limit after thickness increased by re-unsealing. The fluid production daily of the well b1-40-527 was 41.41 t/d and oil production was 1.53 t/d, water cut was 96.3% before the well releasing, then, the well was released firstly in July 2021, total effective thickness released is 6.6 m, after the released, the daily oil production was 1.92 t/d, the daily water cut was 96.3%, and oil production daily increased is 0.39 t/d, which is lower than the requirement of 0.79 t with oil price is 60 $/BBL and ROI is 1:2, therefore, the lower permeability layers were added, the total released thickness is to 10.7 m, which meets the requirement of unsealing, and the daily fluid production of the well b1-40-527 was to 67.79 t/d, the daily oil production was 3.2 t/d, the daily water cut was 95.3%, daily oil production increased was by 1.25 t/d, water cut decreased is 1.0%, and the releasing measure is valid still now.